Rotor steels crack resistance and fracture behavior for hydrogen targeted materials ever-widening database - Balitskii, Alexander I.; Ivaskevich, Lyubomir M.; Balitskii, Olexiy A. (Engineering Fracture Mechanics, 2022)
It has been investigated the influence of hydrogen at pressure up to 10 MPa (and absorbed hydrogen with concentration up to 8.1 ppm) on the strength, ductility, crack resistance of 35NiCrMoV12-5 (38KhN3MFA) rotor steel specimens with different chemical composition and tempering modes. Due to hydrogen embrittlement, the high-pressure gaseous hydrogen (up to 10 MPa) has the most significant influence on rotor steel properties under static tensions, namely relative transverse elongation, reduction of area in smooth cylindrical specimens, fracture toughness in compact samples, and less - on the critical stress intensity factor (SIF) Kfc at cyclic loading. The hydrogen influences the plasticity, static, and cyclic fracture toughness parameters reach the maximum for the ambient temperature. The hydrogen impact on the listed parameters becomes negligible at 530 K. With the increase of the annealing temperature from 923 up to 1023 K structure with larger structural components has formed, lower local stresses increases, the flow boundary decreases and the sensitivity to hydrogen embrittlement under all types of the load is reduced. The SIF diagrams (at static and cyclic loading) were constructed, the crack growth rates on plateau sections were determined. The Paris equation parameters were obtained; all above are valuable tools for the rotors' lifetime prediction. As deducted from stress and strain-controlled S-N curves, hydrogen decreases the high-cycle durability of rotor steel. Hydrogen also decreases the low-cycle durability of rotor steel. The degree of hydrogen effect increases with strain amplitude decrease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: High- and low-cycle fatigue; Hydrogen embrittlement; Rotor steel; Static and cyclic crack resistance